Background extraction using improved mode algorithm for visual surveillance applications. (1st January 2011) - Sivabalakrishnan, M.; Manjula, D.
Background subtraction is a very popular approach for foreground segmentation in a still scene image. A common approach is to perform background subtraction, which identifies moving objects from the portion of a video frame that differs significantly from a background model. In order to compensate for illumination changes, a background model updating process is generally employed, which leads to extra computation time. Background extraction is a fast and efficient moving object segmentation algorithm. This paper presents a novel background extraction algorithm based on improved mode algorithm to obtain the regions of static background, and a novel fuzzy background subtraction approach for video object segmentation. The goal of employing these approaches is to obtain a clean static background reference image and then apply it to background subtraction. We compare our method with other methods and report experimental result.